2010
DOI: 10.1002/ab.20381
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathic personality traits in relational aggression among young adults

Abstract: Psychopathy is a robust predictor of overt physical aggression that may also be relevant to relational aggression (RA). This study was conducted to investigate the utility of psychopathic personality traits in the prediction of RA in a sample of 291 college students. Hierarchical multiple regression analyses indicated that both primary and secondary psychopathic traits explained additional variance in general/peer and romantic RA beyond physical aggressiveness. Consistent with previous research, no gender diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 51 publications
0
29
0
1
Order By: Relevance
“…Internal consistencies for relational aggression and victimization subscales have ranged from .72 to .86 (Czar et al, 2011;Ellis, Crooks, & Wolfe, 2009;Linder et al, 2002;Storch, Bagner, Geffken, & Baumeister, 2004). Ostrov and Houston (2008) reported an alpha of .68 for the prosocial behavior subscale.…”
Section: Self-report Of Aggression and Social Behavior Measurementioning
confidence: 99%
See 1 more Smart Citation
“…Internal consistencies for relational aggression and victimization subscales have ranged from .72 to .86 (Czar et al, 2011;Ellis, Crooks, & Wolfe, 2009;Linder et al, 2002;Storch, Bagner, Geffken, & Baumeister, 2004). Ostrov and Houston (2008) reported an alpha of .68 for the prosocial behavior subscale.…”
Section: Self-report Of Aggression and Social Behavior Measurementioning
confidence: 99%
“…M. Clark et al can be problematic among adults as well. Not only have many of the adverse correlates identified in younger samples been found in studies of emerging adults (e.g., Bagner, Storch, & Preston, 2007;Prinstein, Boergers, & Vernberg, 2001), but associations with antisocial and borderline personality traits, bulimic symptoms, alcohol abuse, impaired prosocial behavior, and a variety of interpersonal problems are also evident (Czar, Dahlen, Bullock, & Nicholson, 2011;Linder, Crick, & Collins, 2002;Miller & Lynam, 2003;Ostrov & Houston, 2008;Prather, Dahlen, Nicholson, & Bullock-Yowell, 2012;Storch, Werner, & Storch, 2003;Werner & Crick, 1999). Prosocial behavior, defined as self-motivated behavior that benefits another person (Eisenberg, 2003), represents a positive alternative to relational aggression and aggression in general.…”
mentioning
confidence: 99%
“…The confluence model of sexual aggression (Malamuth, Linz, Heavey, Barnes, & Acker, 1995;Malamuth, Sockloskie, Koss, & Tanaka, 1991) advantage of others are one of the two aspects of psychopathy, the second being antisocial behaviors (Coid, Yang, Ullrich, Roberts, & Hare, 2009). Previous studies found that people with these psychopathic traits are prone to sexual aggression (Abbey, Wegner, Pierce, & Jacques-Tiura, 2012;Levenson et al, 1995;Mouilso & Calhoun, 2012) and verbal coercion for sexual intercourse (Czar, Dahlen, Bullock, Nicholson, 2011;Muñoz et al, 2011). Based on the confluence model of sexual aggression we hypothesized that psychopathic traits will function as predictors of SBVs.…”
Section: Predictors Of Sbvsmentioning
confidence: 98%
“…In one of the only studies to compare racial groups, there was no difference between White and non-White samples. However, this study examined frequency of aggression and did not examine content; it also combined several different ethnic groups to create a White vs. non-White sample (Czar et al, 2011).…”
Section: The Need For An Intersectional Perspectivementioning
confidence: 99%
“…Some clinical implications have been considered (Sullivan et al, 2010), but there is scarcity of work dedicated to the experiences of women of color in regards to their experiences of relationally aggressive acts (Gomes et al, 2009;Gomes, 2011). There have been calls to expand the body of work both in areas of adult and college student populations (Czar, Dahlen, Bullock, & Nicholson, 2011;Nelson et al, 2008), and in populations of color (Gomes et al, 2009;Gomes, 2011;Neal, 2010;Sullivan et al, 2010). However, little research on relational aggression has moved in this direction.…”
mentioning
confidence: 99%